2018
DOI: 10.1177/1941738118763913
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Valgus Offloading Knee Braces in the Treatment of Medial Compartment Knee Osteoarthritis: A Systematic Review

Abstract: Valgus offloader bracing is an effective treatment for improving pain secondary to medial compartment knee osteoarthritis. The literature remains unclear on the effectiveness of valgus offloader braces with regard to functional outcomes and stiffness. Larger prospective randomized trials with consistent outcome assessment tools and consideration of patient compliance would be beneficial to more accurately determine treatment effects of valgus offloader bracing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 60 publications
2
31
0
Order By: Relevance
“…Duivenvoorden et al [36] further con rmed the conclusions of this study. They conducted a secondary analysis of randomized controlled trial data in 80 patients with KOA, and found no biomechanical evidences to support the use of valgus knee bracing.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Duivenvoorden et al [36] further con rmed the conclusions of this study. They conducted a secondary analysis of randomized controlled trial data in 80 patients with KOA, and found no biomechanical evidences to support the use of valgus knee bracing.…”
Section: Discussionsupporting
confidence: 85%
“…However, the clinical e cacy of valgus knee bracing in the treatment of KOA is not clear. Surprisingly, different studies show opposite outcomes which seriously troubles the selections of physicians in clinic [15][16][17][18][19][20][21][22][23][24][25][26][27][30][31][32][33][34][35][36][37][38]. Therefore, a meta-analysis is urgent to be performed in order to clarify the e cacy of valgus knee bracing.…”
Section: Discussionmentioning
confidence: 99%
“…al suggested a correlation between joint realignment and clinical improvement [37]. However, it was noted that most previous studies concentrated on the clinical effects of valgus bracing in patients with medial knee OA [6,[14][15][16][17]19,38].…”
Section: Plos Onementioning
confidence: 99%
“…A detailed outstanding overview of the current scientific progress and standing can be found in e.g. [2,7,8,15,19]. Studies on knee kinematics have allowed for in-depth analysis of restrictions in movement caused by the brace, improving comprehension of secondary problems, and overall wearability.…”
Section: Introductionmentioning
confidence: 99%
“…Nonpharmacological and nonsurgical interventions can reduce pain and improve physical function in patients with knee OA [7]. Some previous studies show the effectiveness of some interventions such as traditional Chinese medicine (auriculotherapy, acupuncture) and whole body vibration [8], orthotic devises [9], and electrical stimulation [10]. In addition, a systematic review of guidelines for the management of osteoarthritis proposes that exercise is a key factor for treating OA [11].…”
Section: Introductionmentioning
confidence: 99%